Organogenesis of corn plants (Zea mays L.) at various concentrations of auxin and cytokinin plant growth regulators in vitro - Hairuddin, Rahman; Idris, Muh Yusuf; Nur, Kamil (Asian Journal of Agriculture and Rural Development, 2023)
This study aimed to determine the effect of auxin and cytokinin concentrations as plant growth regulators (PGR) on the organogenesis of corn plants in vitro. This research was conducted from June to September 2021 in the plant tissue culture laboratory of Cokroaminoto University, Palopo City, South Sulawesi, Indonesia. The research method was a completely randomized design (CRD) consisting of 15 experimental units, i.e., P0 (control), P1 (2 ml NAA (naphthaleneacetic acid) + 1 ml BAP (benzylaminopurine)), P2 (2 ml NAA + 1.5 ml BAP), P3 (2 ml NAA + 2 ml BAP), and P4 (2 ml NAA + 2.5 ml BAP). The results revealed that the administration of auxin and cytokinin plant growth regulators had a significant effect on the parameters of germination age and plantlet weight, but it had no significant effect on the parameters of plant height, number of roots, root length, and number of leaves. The effective concentration of auxin and cytokinin growth regulators on the organogenesis of corn plants was P2 (2 ml NAA + 1.5 ml BAP) on the parameters of 11 cm plant height, 7 root strands, 1 leaf, and 1 gram plantlet weight. This was due to the influence of the given concentration of PGR, which plays multiple important roles in plant development.